Strengthening Community Resilience through Faith Based Humanitarian Action: A Study of MDMC in Marurinding, West Sulawesi - Muhammad Alifuddin; Nadir La Jamudi; Suarni Suarni; Rosmini Rosmini (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2026)
This study examines how faith-based humanitarian action contributed to strengthening community resilience in Marurinding, West Sulawesi, after the 2021 earthquake. Focusing on the humanitarian practices of the Muhammadiyah Disaster Management Center (MDMC), this study employed a descriptive qualitative approach with an ethnographic orientation. Data were collected through participant observation, in-depth interviews, and document review involving community members, local actors, volunteers, and relevant humanitarian documents. The findings show that the Marurinding community experienced multidimensional disruption, including damaged houses, temporary displacement, limited access to services, fear of aftershocks, and anxiety caused by tsunami-related rumours. MDMC responded through organized service posts, volunteer coordination, logistics distribution, health support, temporary shelter, clean water, sanitation facilities, spiritual reinforcement, disaster education, anti-hoax awareness, and psychosocial activities for children. These interventions helped affected residents regain access to basic needs, safety, reliable information, emotional support, and social confidence. The study also shows that dakwah pencerahan functioned as an ethical foundation for MDMC’s humanitarian practice by translating religious values into inclusive and practical service. Rather than operating as sectarian charity, MDMC’s assistance was coordinated, need-based, and non-discriminatory. This study concludes that faith-based humanitarian action can strengthen community resilience when it combines material support, psychosocial care, disaster education, social trust, and inclusive service delivery.